Dexamethasone-Loaded Pseudo-Protein Nanoparticles for Ocular Drug Delivery: Evaluation of Drug Encapsulation Efficiency and Drug Release - Temur Kantaria; Tengiz Kantaria; Peter Heiduschka; Nicole Eter; David Tugushi; Ramaz Katsarava (Journal of Nanotechnology)
Ophthalmic drug delivery for treating various eye diseases still remains a challenge in ophthalmology. One perspective way of overcoming this problem is to use nanoscale biodegradable drug carriers that are able to safely deliver pharmaceuticals directly to the locus of disease and maintain a therapeutic concentration of drug for a long time. The goal of the present study was the preparation of drug- (dexamethasone-, DEX-) loaded pseudo-protein nanoparticles (NPs) and investigation of drug encapsulation efficiency and drug release kinetics. DEX-loaded pseudo-protein NPs (DEX-NPs) were successfully prepared by the nanoprecipitation method. DEX-NPs were characterized by size (average diameter, AD), size distribution (polydispersity index, PDI), and surface charge (zeta-potential, ZP) using the dynamic light scattering technique. DEX encapsulation characteristics were determined using the UV-spectrophotometric method, and kinetics of DEX release from DEX-NPs was studied according to the dialysis method in PBS at 37°C. The obtained results showed that size of DEX-NPs varies within 143.6–164.1 nm depending on DEX content during the preparation. DEX incorporation characteristics were determined—encapsulation efficiency (EE) and actual drug loading (DL) were high enough and reached 55.1 and 10.2%, respectively. The kinetics of DEX release from DEX-NPs showed a typical biphasic release pattern—an initial rapid (burst) release and further much more continuous slow release. Based on the obtained data, we can conclude that the elaborated DEX-NPs have potential for the application in ophthalmology as ocular drug delivery nanocarriers.